The effect of light curing intensity on dentin bond strength of a dual-cure resin cement polymerized under a lithium disilicate ceramic - Chuenban, Krongpon; Senawongse, Pisol; Saikaew, Pipop; Kaophun , Saowaros; Churnjitapirom, Pornkiat (Mahidol Dental Journal, 2025)
Objectives: To evaluate the impact of different light curing intensities on the bond strength of dual-cure resin cement under lithium disilicate ceramic. Materials and Methods: Thirty-third molars were sectioned to expose midcoronal dentin, divided into three experimental groups with 10 specimens. Each group was bonded to truncated cone-shaped lithium disilicate ceramics using Panavia V5 dual-cure resin cement that were polymerized with 3 conditions: group 1, no light-curing, group 2, light cured with High mode (1123±4.83 mW/cm²), and with Turbo mode (1981±11.00 mW/cm²) in group 3. The light-curing for 60 seconds was used in this study. After 24 hours, the degree of conversion (DC) was measured on both primer and cement sides using a Raman spectrometer, and all bonded specimens underwent a tensile bond strength test. Results: The uncured cement showed the lowest DC (70.88±0.55%), while light-curing significantly increased DC (High mode: 73.56±0.25%, Turbo mode: 75.94±0.61%). No significant differences were found in DC on the primer side of cement for uncured, High mode, and Turbo mode (98.91±0.04%, 98.92±0.03% to 98.93±0.03% accordingly). Mean TBS for groups 1, 2, and 3 were 5.53 MPa, 11.27 MPa, and 14.52 MPa, respectively, showing significant differences. Conclusion: DC improved significantly with light curing on the cement side, though it did not affect the adhesive side. The tensile bond strength was enhanced with increased light curing intensity.